Volatility spillover effects during pre-and-post COVID-19 outbreak on Indian market from the USA, China, Japan, Germany, and Australia - Mohanasundaram Thangamuthu; Suneel Maheshwari; Deepak Raghava Naik (Journal of Risk and Financial Management, 2022)
We examined volatility spillover effects from five prominent global stock markets to India's stock market during the pre-and-post COVID-19 outbreak using daily adjusted closing prices between January 2019 and September 2021 from six capital markets. The structural breakpoint was identified as 23 March 2020, as per the breakpoint unit root test, to examine and compare the results pre-and-post COVID-19. Results show that previous period news and volatility feeds the next period's volatility significantly and the volatility is found to be persistent. The analysis also shows that during the pre-COVID period there is a negative significant volatility spillover from four of the five selected stock markets (Australia, China, Japan, and Germany) to the Indian stock market, and that spillover continues in the post-COVID period. There is a positive significant return and volatility spillover from the US market to the Indian stock market in the post-COVID-19 period. The results of our study will be useful for retail investors and portfolio managers in understanding the portfolio allocation methods in case of volatility spillover arising due to the crisis caused by the COVID-19 outbreak.
Keywords: 650; COVID-19; volatility; EGARCH; investment; stock returns; asymmetry; spillover